Alterations in Cardiac Vagal Modulation-to-Vagal Tone Ratio in response to accumulated exercise stress in intermittent team sport - Perrotta Andrew S.; Warburton Darren E.R (Sciendo, 2020)
Study aim: This investigation examined the cardiac vagal modulation-to-vagal tone ratio and its utility to represent the dose response to accumulated exercise stress in intermittent team sport.